The dolphin letters, 1970-1979 : Elizabeth Hardwick, Robert Lowell and their circle - Hamilton, Saskia, 1967-; Hardwick, Elizabeth; Lowell, Robert, 1917-1977 (Farrar, Straus and Giroux, 2019)
"The letters of Elizabeth Hardwick and Robert Lowell offer an unprecedented portrait of two of the biggest names in twentieth-century literature"--